Výroba tělesa AC/DC adaptéru - Vašíček, Lukáš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2021)
Bakalářská práce navrhuje vstřikovací formu na výrobu plastového adaptéru. Na základě zhodnocení technologických možností výroby plastového výrobku, byla vybrána technologie vstřikování plastů. První část práce je věnována teoretickému vysvětlení plastových materiálů, vstřikovacích forem a strojů. V praktické části je uveden a vypracován kompletní návrh vstřikovací formy včetně volby vhodného materiálu. Forma je koncipována čtyřnásobně se studenou vtokovou vložkou. V závěru práce je provedeno technicko – ekonomické zhodnocení výroby.

The bachelor's thesis proposes an injection mold for the production of a plastic adapter. Based on the evaluation of the technological possibilities of the production of a plastic product, the technology of plastic injection was chosen. The first part of the work is devoted to a theoretical explanation of plastic materials, injection molds and machines. The practical part presents and develops a complete design of the injection mold, including the selection of a suitable material. The mold is designed four times with a cold inlet insert. At the end of the work is a technical - economic evaluation of production.
Manufacture of AC / DC adapter housing
Keywords: vstřikovací forma; adaptér; plasty; vstřikování plastů; technologie; injection mold; adapter; plastics; plastic injection; technology